Long-term organic fertilizer substitution increases rice yield by improving soil properties and regulating soil bacteria - Liu, Jiai; Shu, Aiping; Song, Weifeng; Shi, Wenchong; Li, Mingcong; Zhang, Wenxue; Li, Zuzhang; Liu, Guangrong; Yuan, Fusheng; Zhang, Shuxin; Liu, Zengbing; Gao, Zheng (Geoderma, 2021)
[Display omitted] •Long-term organic fertilizer substitution improved soil nutrients and reduced soil acidification.•Long-term organic fertilizer substitution changed the composition and functions of soil bacterial community.•Soil nutrients were the main contributors to increasing rice yield.•Microorganisms indirectly increased yield through soil enzyme activity and nutrients. Applying organic and inorganic fertilizers together could sustainably increase crop yields. The effects of long-term organic fertilizer substitution on soil microbial community structure and function in paddy soil and on rice yield remain unclear. We evaluated changes in soil physicochemical factors, bacterial community structure responses, and the contributions of soil properties and bacterial communities to rice yield after 34 years of different fertilization treatments. A high ratio of organic fertilizer substitution significantly reduced soil acidification, improved soil nutrients, and increased soil urease and catalase activities (P < 0.05). Organic fertilizer substitution significantly changed the soil bacterial community structure and increased the relative abundance of beneficial bacteria, such as Bacilli and Flavobacteriales. The highest proportion of organic substitution treatment significantly enhanced carbon-related functional groups (P < 0.05), like aromatic hydrocarbon degradation and chitinolysis. The biomarkers enriched in the inorganic treatment and the organic fertilizer substitution treatments had similar correlated environmental factors but opposite correlation trends. Soil nutrient levels, especially total nutrients, explained most of the variation in annual rice yield, while bacteria indirectly affected annual yield through enzyme activities and nutrient levels. Our results provide evidence that soil nutrients and bacteria contribute to rice yield increase in long-term organic fertilizer substitution treatment.